Ius hospitii y ius civitatis - Balbín Chamorro, Paloma (Gerión. Revista de Historia Antigua, 2006)
This work analyzes the relation between ius hospitii and ius civitatis, represented in the Hispanic epigraphy by three inscriptions which specify citizenship rights, in addition to hospitia, for the signers of the pacts. The hypothesis formulated by Humbert is taken again. This author sustained that, in the archaic Latium, the hospitium publicum gave a potential citizenship to the hospes in the sense that, it did not suppose a change of citizenship, but the enjoy of certain rights which became effective only while the beneficiary was in the territory of the community that welcomed him. One thoroughly reading of the sources let us sense that such rights had to do with commitments of mutual help, as well as with the exchange of passing rights that would make possible, between others, the performance of economic activities that required to go through the limits of the own territory, and to enter in those of the border communities.